Patient satisfaction and treatment adherence of stable human immunodeficiency virus-positive patients in antiretroviral adherence clubs and clinics - Gabi A. De Jager; Talitha Crowley; Tonya M Esterhuizen (AOSIS, 2018)
Background: South Africa has experienced a substantial increase in access to antiretroviral treatment (ART) in recent years. Effective strategies to manage access to treatment need to be incorporated into and implemented in ART programmes. Antiretroviral treatment adherence clubs are a new strategy that is being implemented in various parts of South Africa. Aim: The aim of the study was to investigate treatment adherence and patient satisfaction of stable human immunodeficiency virus (HIV) patients on ART in ART adherence clubs and clinics. Setting: The study was conducted in the Eden district of the Western Cape, South Africa. Methods: A cross-sectional analytical study was conducted to examine the relationships between patient satisfaction and treatment adherence in ART adherence clubs and clinics in the Eden district, Western Cape province, South Africa. Validated questionnaires were used to measure patient satisfaction and self-reported treatment adherence. Results: The study included 320 participants (98 club and 222 clinic) from 13 primary health care clinics. The analyses showed that higher levels of satisfaction could be predicted with club participants compared to clinic participants (p = 0.05). There was no significant difference between clinic and club participants with regards to treatment adherence. However, being adherent was more likely in participants who were satisfied (odds ratio = 3.18, 95% confidence interval [1.14-7.11], p < 0.01). Conclusion: Antiretroviral treatment adherence clubs provide a service that patients are more satisfied with although they are not more adherent to treatment. This strategy may be effective for the delivery of long-term care for patients on ART.